Nutritional potential analysis and development of local food-based MP-ASI formula as a specific intervention for stunting prevention - Ayudia, Esa Indah; Hafizah; Iskandar, Mirna Marhami; Gading, Patrick Wiliam; Asty, Zahra Frizki; Veonika, Dea Anenta; Hardiningsih, Denok Tri; Miftahurrahmah; Hz, Tia Wida Ekaputri Hz (Proceedings Academic Universitas Jambi, 2025)
Background: Stunting is a chronic malnutrition problem that has implications for the failure of growth and development of toddlers, mainly caused by prolonged nutritional deficiencies during the critical period of the First 1000 Days of Life (HPK). Specific nutritional interventions that are essential in the post-exclusive breastfeeding period are the provision of Complementary Breastfeeding Foods (MP-ASI) that meet the principles of Adequate, Timely, Safe, and Correct. Objective: The purpose of this research is to identify, analyze nutritional potential, and optimize the use of local food ingredients to support the preparation of MP-ASI formulas to prevent stunting in the working area of the Olak Kemang Community Health Center, Jambi City. Methods: The method applied is qualitative-participatory through participatory-based education and training, with measurement of increased maternal nutritional literacy using pre-tests and post-tests. Results: The results of the identification of local food availability show high nutritional potential, where Tempe has the highest protein content (20.8 g/100g), followed by Patin Fish (17.0 g/100g), and Red Spinach, which is rich in Iron (7.0 mg/100g). Conclusion: The implementation of this program successfully improved nutritional literacy and mothers’ skills in producing nutritious complementary foods based on local wisdom. This is an effective and sustainable strategy for improving nutritional status and accelerating the reduction in stunting prevalence.